Reduction of Oxidative/Nitrosative Stress in Brain and its Involvement in the Neuroprotective Effect of n-3 PUFA in Alzheimer’s Disease - Serini, Simona; Calviello, Gabriella (Current Alzheimer Research, 2016)
Plenty of evidence has shown that an enhanced oxidative or nitrosative stress may play a central role in the pathogenesis of neurodegenerative disorders such as Alzheimer’s disease (AD). The suppressive effect of n-3 polyunsaturated fatty acids (n-3 PUFA) against oxidative/nitrosative stressinduced injury in nervous tissues has recently received increasing interest. A number of human experimental studies have concurred to demonstrate that they may exert a substantial preventive role, especially in the very early phase of mild cognitive impairment (MCI) preceding AD. It has been suggested that they may exert an indirect antioxidant/anti-nitrosative role by modulating the expression/ activity of several proteins involved in the modulation of oxidative stress in nervous tissues. In particular, recent data have supported the hypothesis that in the early phase of MCI the light to moderate oxidative stress triggered by not cytotoxic doses of n-3 PUFA can positively regulate the transcriptional activity of nuclear factor erythroid 2-related factor 2 (Nrf2). This may result in the induced expression of heme oxygenase-1 (HO-1) and other antioxidant proteins transcriptionally regulated by Nrf2. Alternatively, the anti-inflammatory and antioxidant/anti-nitrosative effects of n-3 PUFA have been lately related to their ability to blunt microglia persistent activation occurring during chronic inflammation involved in the pathogenesis of neurodegenerative diseases. Evidences have been presented that n-3 PUFA may convert microglia from the macrophage M1 to an M2 phenotype showing lower production of neurotoxicoxidative factors and enhanced phagocytic activity toward Aβ peptide, or even to a further phenotype with neurotrophic/ protective properties.
Keywords: antioxidant